Aprendizaje basado en proyecto y su influencia en el desarrollo de habilidades críticas en los estudiantes 7mo EGB de la Parroquia Vinces del Cantón Vinces periodo lectivo 2024-2025 - Rios Cando, Ines Jeaneth (2025)
Project-based learning, also known as (PBL), is a methodology for the teaching-learning process that focuses especially on students, so that it promotes the active participation of students through the execution of a project that is carried out based on a problem identified in the real world for its prior resolution. On the other hand, PBL motivates the student to be the protagonist of knowledge, in such a way that it promotes the development of critical skills and problem solving through practice. The present research is oriented to the influence of project-based learning on the development of critical skills in 7th grade students from the Doctor José María Velasco Ibarra EGB schools and the Doctor Lorenzo Rufo Peña school in the Vinces parish. The objective of the research is to carry out an in-depth study through theoretical review and analysis of the different aspects or perspectives that underpin PBL in the development of students' critical skills. Therefore, a methodology based on descriptive and exploratory research is used with a mixed approach that allows the collection of data and opinions from both teachers and students, in order to point out learning and its relationship with critical skills, in addition to the design of this research is based on documentary research from reliable sources and field research for the analysis of the institutions linked to the object of study.